Factors Affecting Vaccine Distribution Activities For The Community With Door To Door Method - Chatarina Hatri Istiarini; Resta Betaliani Wirata; Nurlia Ikaningtyas; Ratna Puspita Adiyasa (Poltekkes Kemenkes Surakarta, 2022)
Background: The